Kricagem indicativa para elaboração de mapas probabilístico em agricultura de precisão - Fernandes, Talita Tanaka [UNESP] (2014)
The main purpose of this paper is to apply non-linear geostatistical methodology, speci cally Indicator Kriging, to create probability maps of occurrence of soil variables. The idea is to contribute for the improvement and correction of inputs in planting areas, reducing costs and negative environmental impacts and thereby increase agricultural productivity. This methodology was applied to the region of the basin area of the Araqu a River, located in the municipalities of S~ao Manuel and Botucatu - S~ao Paulo State, Brazil, generating probability of occurrence maps of phosphorus, potassium and base saturation, according to the texture of the soil (sandy and clay) for sugar cane plantation, predominant crop in the area. The kriging technique was e cient to generate probabilistic maps to the studied variables, showing the areas in need of a particular soil amendment or not. The central area of the region is predominantly clay soil, also this is an area that is larger amounts of phosphorus, potassium and base saturation. It is also worth noting that the variables were not normally distributed, but the presence of anomalous values/outliers, which highlights the practicality and ease use of this technique